Introduction to protein informatics - Zimmermann Karl-Heinz (Boston Kluwer Academic, 2003)
The text emphasizes mathematical and computational methods to tackle the central problems of alignment, phylogenetic reconstruction, and prediction and sampling of protein structure.
Keywords: Bioinformatics; Protein informatics